GOOD GOVERNANCE DALAM PELAYANAN KESEHATAN PADA PUSKESMAS BATU 10 KOTA TANJUNGPINANG TAHUN 2017-2018 - Dian Perdana Putra; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The implementation of good governance in terms of service and fulfillment of needs for the community is an agency is an indicator of achieving a more directed goal of bureaucracy. One of them is through basic health services provided at Batu 10 health center so that the community can meet the highest level of health that can be seen through the performance of health workers in any matter related to public services, health checks, treatment, and prevention of disease to patients or communities who are required to provide the best service, through technical work which is based on the suitability of SOPs, legal provisions, application of work culture and minimum service standards that apply. This research is to see how health services at Batu 10 health center through the UKP and UKM aspects and to see how far Batu 10 health center it can be said that agencies have implemented good governance indicators. The theory used in this study is good governance and service. The research method used is a qualitative research method using descriptive methods.Based on the explanation above, then this study found that; first health service at Batu 10 health center can be said to be optimal, but it still needs a lot of evaluation in services related to discipline, responsibility, coordination, and must communicate more frequently to the community in order to reduce the form of complaints and avoid losses to other parties or Own health center; second Batu 10 health center can be said to have implemented indicators on good governance, both from the aspects of participation, transparency, accountability, effective and efficient as well as strategic vision. But before accreditation, Batu 10 health center still experienced quite a number of fatal problems, then after the accreditation it could be said that the Puskesmas did a lot of repairs. In the aspect of legal certainty there is still an injustice in providing services that are not equal.Keywords: Health Servive, Good Governances, Health Center